2022
DOI: 10.1055/s-0042-1758751
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth for Parkinson disease patients during the COVID-19 pandemic: the TeleParkinson study

Abstract: Background Telemedicine allows Parkinson disease (PD) patients to overcome physical barriers to access health care services and increases accessibility for people with mobility impairments. Objective To investigate the feasibility indicators of a telehealth intervention for PD patients, including patient recruitment, attendance, technical issues, satisfaction, and benefits on levels of physical activity and sleep. Methods We conducted a single-center, single-arm study of telehealth video co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Studies in low- and middle-income countries found telehealth services reduced travel time, prevented unnecessary visits and travel expenses associated with it, detected complications early, provided an early response to emergencies, e-prescriptions, more personalised attention, and increased accessibility in rural areas [ 16 , 21 , 25 , 32 , 36–41 ]. For example, a study in Brazil reports average travel time saved as a result of telehealth was 289.6 minutes, which accounted for R$106.67 saved [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in low- and middle-income countries found telehealth services reduced travel time, prevented unnecessary visits and travel expenses associated with it, detected complications early, provided an early response to emergencies, e-prescriptions, more personalised attention, and increased accessibility in rural areas [ 16 , 21 , 25 , 32 , 36–41 ]. For example, a study in Brazil reports average travel time saved as a result of telehealth was 289.6 minutes, which accounted for R$106.67 saved [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the reviewed literature, though we found telehealth services to be effective in many low- and middle-income countries, few studies found it to have no significant difference when compared with the existing system. Studies in Bangladesh on behavioral intention, in Brazil on mitigating the psychological impact of COVID-19, cerebral palsy, and Parkinson’s disease, in China on dementia, hypertension, and type 2 diabetes management, on emergency mHealth use, on retinopathy of prematurity and psychological distress, in Montenegro on neurosurgical care, in Paraguay on postoperative follow-up, in Thailand on type 2 diabetes and Turkey on autoimmune hepatitis, phenylketonuria, breathing exercise, type 2 diabetes, and mental health found a significant improvement in the healthcare services when telehealth services were employed compared to no implementation during the COVID-19 pandemic [ 23 , 24 , 27 , 41 , 43 , 44 , 56–68 ]. However, studies in Egypt on anticoagulants and myocardial infarction,in Georgia on self-injury, in Tunisia on children and adolescent arthritis, in Argentina on epilepsy, and in Brazil on type 2 diabetes management found no significant differences in healthcare service utilisation and overall health outcomes with the implementation of telehealth services [ 33 , 36 , 47 , 50 , 51 , 69 ].…”
Section: Discussionmentioning
confidence: 99%